2009
DOI: 10.1002/joc.2024
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of the magnitude, frequency and distribution of intense rainfall in the United Kingdom

Abstract: During the 1960s, a study was made of the magnitude, frequency and distribution of intense rainfall over the United Kingdom, employing data from more than 120 daily read rain gauges covering the period 1911 to 1960. Using the same methodology, that study was recently updated utilizing data for the period 1961 to 2006 for the same gauges, or from those nearby. This paper describes the techniques applied to ensure consistency of data and statistical modelling. It presents a comparison of patterns of extreme rain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Both Min et al (2011) and Westra et al (2013) concluded that a statistically significant increase in the annual maximum daily precipitation can be detected on a global basis. For Northern and Central Europe a number of recent studies exists for various regions; Belgium (Ntegeka and Willems 2008), Czech Republic (Kysely 2009), Denmark (Gregersen et al 2013a), Germany/Poland (Lupikasza et al 2011), Sweden (Bengtsson andRana 2013) and UK (Rodda et al 2010). Depending on season, region within the country and analysed indices, they all detect changes in heavy rainfall.…”
Section: Introductionmentioning
confidence: 99%
“…Both Min et al (2011) and Westra et al (2013) concluded that a statistically significant increase in the annual maximum daily precipitation can be detected on a global basis. For Northern and Central Europe a number of recent studies exists for various regions; Belgium (Ntegeka and Willems 2008), Czech Republic (Kysely 2009), Denmark (Gregersen et al 2013a), Germany/Poland (Lupikasza et al 2011), Sweden (Bengtsson andRana 2013) and UK (Rodda et al 2010). Depending on season, region within the country and analysed indices, they all detect changes in heavy rainfall.…”
Section: Introductionmentioning
confidence: 99%
“…Jenkins et al (2008) also report a decrease in rainfall during the summer season and an increase in winter rainfall, with a particular increase of high-rainfall events in winter. As Rodda et al (2010) point out, it is difficult to discern whether or not the observed changes in extreme rainfall pattern can be linked to human activities, as the signal for change can be quite variable. The appropriate methodology and approaches used in trend studies are still a debated issue: the same direction of a signal in a data series can be identified by different methods, but these might give contrasting indications when it comes to evaluating the statistical and practical significance of the estimated signal; see Lins and Cohn (2005) for a full commentary on this.…”
Section: Prosdocimi Et Al: Non-stationarity In the Ukmentioning
confidence: 99%
“…Using the same methodology, we updated that study utilizing data for the period 1961 to 2006 for the same gauges, or from those nearby (Rodda et al, 2010). The purpose of updating the study was to investigate the changes in the patterns of extreme rainfalls for the two periods.…”
Section: Quantifying the Risk Of Extreme Eventsmentioning
confidence: 99%
“…A wide range of practical applications rely on information about the likelihood of extreme rainfall events (Rodda, 1967(Rodda, , 1972Hand et al, 2004). This information can be obtained by investigating the relationship between magnitude, frequency and distribution of intense rainfall (Coles, 2001).…”
Section: Introductionmentioning
confidence: 99%